PENINGKATAN KUALITAS HIDUP PADA PENDERITA GAGAL GINJAL KRONIK YANG MENJALANI TERAPI HEMODIALISA MELALUI PSYCHOLOGICAL INTERVENTION DI UNIT HEMODIALISA RS ROYAL PRIMA MEDAN TAHUN 2016 - Emma Feronika Hutagaol (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2017)
ABSTRACT The chronic renal failure was a problem important, prevalence and evidence based to improve. Patients were chronic renal failure improvement of the quality of patients with undergoing hemodialysis. The purpose of this study was to determine the increase in the quality of life of patients with chronic renal failure undergoing hemodialysis therapy through psychological intervention at the Hemodialysis Unit, Royal Prima Hospital Medan in  2016. This type of research is pre experiment with the design of one group pre-post test design. This research was conducted in June 2016. The samples of this study were 12 patients suffering from chronic renal failure drawn by purposive sampling technique. Based on the results of this study, it is indicated that the quality of life before psychological intervention on (pre-test) the average was 2.58 with a standard deviation of 0.515. While the quality of life is better after the psychological intervention (post-test) the average was 1.50 with a standard deviation of 0.674. Based on statistical test of Wilcoxon, it was obtained that  p-value 0.002 (<0.05), meaning there is a significant increase in quality of life between psychological intervention and quality of life of patients with chronic renal failure undergoing hemodialysis.The conclusion of this study states that there is an improvement of the quality of patients with chronic renal failure undergoing hemodialysis to psychological intervention through devotions and spiritual relaxation can be used as an alternative spiritual therapy to improve the quality of life of patients with chronic renal failure undergoing hemodialysis. Keywords : Psychological Intervention, Quality of Life, People with CRF, Hemodialysis